2016
DOI: 10.5194/acp-16-12993-2016
|View full text |Cite
|
Sign up to set email alerts
|

The regional impact of urban emissions on climate over central Europe: present and future emission perspectives

Abstract: Abstract. The regional climate model RegCM4.2 was coupled to the chemistry transport model CAMx, including twoway interactions, to evaluate the regional impact of urban emission from central European cities on climate for presentday (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) and future (2046)(2047)(2048)(2049)(2050)(2051)(2052)(2053)(2054)(2055) periods, and for the future one only emission changes are considered. Short-lived non-CO 2 emissions are considered and, for the future impact, only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 92 publications
(100 reference statements)
8
25
2
Order By: Relevance
“…The average urban canopy impact on temperature is very similar to the values presented in Huszar et al (2018a) who, for the two analyzed cities (Berlin and Prague), encountered increases up to 1.5-2 • C. The diurnal variation of the impact shows also large similarities in both the quantitative and qualitative sense, when the maximum impact occurs around late evening. The urban impact on temperature is consistent with previous observation (Gaffin et al, 2008) and model-based studies (Pichierri et al, 2012;Giannaros and Melas, 2012;Struzewska and Kaminski, 2012), while Sarrat et al (2006) simulated somewhat later timing of the maximum urban impact.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The average urban canopy impact on temperature is very similar to the values presented in Huszar et al (2018a) who, for the two analyzed cities (Berlin and Prague), encountered increases up to 1.5-2 • C. The diurnal variation of the impact shows also large similarities in both the quantitative and qualitative sense, when the maximum impact occurs around late evening. The urban impact on temperature is consistent with previous observation (Gaffin et al, 2008) and model-based studies (Pichierri et al, 2012;Giannaros and Melas, 2012;Struzewska and Kaminski, 2012), while Sarrat et al (2006) simulated somewhat later timing of the maximum urban impact.…”
Section: Discussionsupporting
confidence: 82%
“…Figure 18 presents the JJA changes of O 3 due to the urbanization-induced K v enhancement for the three resolutions and six K v methods. Ozone is increased in all cases, ranging from 0.2 to 3 ppbv (about 5 %-10 %), as expected following Huszar et al (2018a). They showed that the main contributor to this increase is the reduced destruction due to the turbulence-enhanced vertical removal of NO x from the canopy layer and the increased turbulent flux from the RL during the night.…”
Section: The Effect Of Perturbed Diffusivitiessupporting
confidence: 59%
See 3 more Smart Citations